KEBIJAKAN PEMERINTAH PROVINSI RIAU TERHADAP IMPLEMENTASI REDD+ (Reducing Emission from Deforestation and Forest Degradation Plus) DI RIAU - Maharani "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is aimed to explain REDD+ system as one of the resolution of problems instrument in reducing greenhouse gas emissions. Research was located in Riau Province, due to its historically high deforestation. Land Use, Land Use Change and Forestry (LULUCF) which have contributed 17-20% to concentration of greenhouse gas (GHG) in atmosphere and climate change. This figure is bigger than global forest area in the world, particularly in comparison with the existing tropical forest that is only around 10% of global forest area in the world. One of mechanism for reducing GHG is through Reducing Emissions from Deforestation and Forest Degradation Plus (REDD+). This research was built by using theory of human security and sustainable development. Data analysis was used with stakeholder analysis and descriptive analysis. The method used in this study is descriptive, which explains or depicts and interprets the data later to compare and examine factors related to the situation, conditions and phenomena. The research found that REDD+ involvement in the implementation of the parties strongly supported the implementation of these activities and also needed special attention in the area of spatial management. The provincial government conducts policy by way of involved stakeholder as local and indigenous communities..Key Word: Riau, Green House Gas (GHG), REDD+, LULUCF, Human Security, Sustainble Development, Stakeholder